Distinct Phenotypes of Shank2 Mouse Models Reflect Neuropsychiatric Spectrum Disorders of Human Patients With SHANK2 Variants - Eltokhi, Ahmed; Rappold, Gudrun; Sprengel, Rolf (Frontiers in Molecular Neuroscience, 2018)
The SHANK scaffolding proteins are important organizers for signaling proteins in the postsynapse of excitatory neurons. The functional significance of SHANK proteins becomes apparent by the wide spectrum of neurodevelopmental and neuropsychiatric disorders associated with SHANK variants in human patients. A similar diversity of neuropsychiatric-like phenotypes is described for numerous Shank2 and Shank3 knockout (KO) mouse lines. In this review, we will focus on and discuss the experimental results obtained from different, but genetically related and therefore comparable, Shank2 mouse models. First we will describe the distinct SHANK2 variant-mediated neurodevelopmental and neuropsychiatric disorders in human patients. Then we will discuss the current knowledge of the expressed SHANK2 isoforms in the mouse, and we will describe the genetic strategies used for generating 3 conventional and 7 conditional Shank2 mouse lines. The distinct impairments i.e. autistic-like and mania-like behavior and the alterations on the molecular, electrophysiological and behavioral levels will be compared between the different Shank2 mouse models. We will present our view as to why in these mouse models a spectrum of phenotypes can arise from similar Shank2 gene manipulations and how Shank2 mutant mice can be used and should be analyzed on the behavioral level in future research